Long-term mean (1985-2015) 30-m vegetation phenology data (Chicago metropolitan) - Xuecao Li; Yuyu Zhou; Lin Meng; Ghassem Asrar; Chaoqun Lu; Qiusheng Wu (PANGAEA, 2019)
This data set includes: "Chicago_longTerm_mean_SOS" & "Chicago_longTerm_mean_EOS": long term (1985-2015) mean SOS and EOS derived from the Double Logistic Model; "Chicago_longTerm_mean_Correlations": performance of double logistic model "Chicago_AnnualSOS_*": annual SOS measured from the long term mean SOS